Native Argentinean cyclopoids (Crustacea: Copepoda) as predators of Aedes aegypti and Culex pipiens (Diptera: Culicidae) mosquitoes - C. Tranchida, María (2009)
Copepods from La Plata, Argentina were investigated to characterize the local community of larvivorous copepods inhabiting mosquito breeding sites and to identify new predator species of the mosquitoes which occur in artificial containers, Aedes aegypti and Culex pipiens. Diversity of larvivorous cyclopoids was highest in permanent pools. Predation by sex and age, selectivity on mosquito species, and daily predation rate during five days were studied for Acanthocyclops robustus, Diacyclops uruguayensis, Macrocyclops albidus and Mesocyclops longisetus. Female copepods presented the highest predatory capacity. No predatory preference for mosquito species was found. According to overall predation potential, copepods were ranked as follows: D. uruguayensis < A. robustus < M. albidus < M. longisetus. Copepod tolerance to desiccation and capacity to survive in water from artificial containers were also evaluated. D. uruguayensis and A. robustus survived under dry conditions, but D. uruguayensis showed lower survival in water from cemetery flower vases. M. albidus did not survive under dry conditions and did not tolerate water extracted from artificial containers. M. longisetus survival was not severely reduced after desiccation or breeding in water from flower vases. The Neotropical cyclopoids D. uruguayensis and A. robustus can be considered good candidates and merit further research as biological control agents for mosquitoes.